Failure To Realize Constitutional Goals In Cyberspace: A Constitutional Law Review Of The National Data Center (PDN) Data Breach Incident - Roul Alvaro Prasetyo; Eny Kusdarini; Muhammad Kamil Ridha (SOSIOEDUKASI, 2026)
The digital transformation of government services through the National Data Center (PDN) aims to realize effective and responsive public administration. However, a massive ransomware attack on the PDN in mid-2024 revealed a fatal vulnerability in Indonesia's cybersecurity governance architecture, paralyzing essential services and harming millions of citizens. This study analyzes the state's negligence in managing the PDN from a Constitutional Law perspective, evaluating it through the fulfillment of the functions, objectives, and supremacy of the constitution. This research employs a normative legal method using statutory and conceptual approaches. The findings indicate that the data breach at the PDN is not merely a technical IT failure, but a representation of a fundamental constitutional failure. First, the state failed to realize the constitutional objective of protecting the Indonesian nation as mandated by the Fourth Paragraph of the 1945 Constitution, and failed to guarantee the basic right to personal data protection enshrined in Article 28G Paragraph (1). Second, overlapping authority and blame-shifting between the Ministry of Communication and Informatics and the National Cyber and Crypto Agency (BSSN) demonstrate the failure of the constitution's function in limiting power and demanding institutional accountability. Third, the government's delay in establishing an independent Personal Data Protection Supervisory Authority, as mandated by Law No. 27 of 2022, constitutes an anomaly of constitutional supremacy, where the rule of law is defeated by bureaucratic sluggishness. This study recommends the immediate establishment of an independent supervisory agency, optimization of legislative oversight, and strict legal accountability for state institutions.